2019
DOI: 10.1186/s12944-019-1003-x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene polymorphism and renal function are associated with apolipoprotein E concentration in patients with chronic kidney disease

Abstract: Background: Chronic kidney disease (CKD) associates with complex lipoprotein disturbances resulting in high cardiovascular risk. Apolipoprotein E (APOE) is a polymorphic protein with three common isoforms (E2; E3; E4) that plays a crucial role in lipoprotein metabolism, including hepatic clearance of chylomicrons and very low-density lipoprotein (VLDL) remnants, and reverse cholesterol transport. It demonstrates anti-atherogenic properties but data concerning the link between polymorphism and level of APOE in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Alterations of lipid profile could be associated with acceleration of atherosclerosis and higher risk of incident CVD. 30 Moreover, obesity, smoking, etc. conditions associated with high oxidative stress, can aggravate the progression of disease and genetic studies can thus provide information that may help to improve the ability to identify individuals, families and populations at increased risk, and to improve the clinical management of patients of MI.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations of lipid profile could be associated with acceleration of atherosclerosis and higher risk of incident CVD. 30 Moreover, obesity, smoking, etc. conditions associated with high oxidative stress, can aggravate the progression of disease and genetic studies can thus provide information that may help to improve the ability to identify individuals, families and populations at increased risk, and to improve the clinical management of patients of MI.…”
Section: Resultsmentioning
confidence: 99%
“…The precise cellular mechanisms which are responsible for the differences between ε2, ε3 and ε4 are not fully understood, but ε4 has a somewhat higher affinity for the LDL receptor than ε3, while ε2 bind less well to the receptor-only 2% of normal activity, which results in different plasma lipoprotein profiles. 19 ε4 is associated with elevated levels of TC, LDL-C, TG and ApoB, lower plasma levels of ApoE, and an increased CAD incidence. 20 , 21 A large meta-analysis demonstrated that ε2 carriers have a 20% lower CAD risk compared with ε3 or ε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“… 35 We also observed that ɛ4 carriers had a significantly lower ApoE in both groups, which was consistent with previous findings of the ApoE level being highest in ɛ2 carriers and lowest in ɛ4 carriers. 19 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Another age-moderated protein, APOE stands out as having previously reported agerelated associations with disease and organ dysfunction, in both cases including Alzheimer's Disease (AD). APOE plays an important role in lipid metabolism to regulate the growth and survival of mesangial cells and preserve kidney function 49 ; not only is APOE protein a marker for outcome in transplant recipients [50][51][52] , there is also evidence for particular APOE genetic alleles being associated with dysfunction risk [53][54][55] , possibly manifested directly by lipidomic differences between allelic profiles 56 . APOE alleles are further implicated in a host of disorders including age-moderated association with AD risk 57 (with the strongest effect manifesting around age 65 58 ), macular dysfunction, atherosclerosis and pulmonary scarring 59,60 .…”
Section: Discussionmentioning
confidence: 99%